Аналіз світового досвіду організації luxury послуг в 5* готелях - Мирошник, Юлія Анатоліївна (My University, 2019)
Метою статті є оцінка якості послуг “butler service” засобів розміщення України, порівняння з закордонним досвідом. Методика. Статистичною основою роботи виступають праці вітчизняних авторів у сфері готельного господарства, наукова періодика, ресурси Інтернет-мережі. General formulation of the problem. The hotel business is quite promising today in development and investing. This is facilitated by the rapid development of technology in the field of hospitality that set for the hoteliers two main objectives: to attract the maximum number of customers by optimizing sales and to conquer the clients by making them regular guests. In the hotel business only accommodation facilities offering their guests quality hotel services that can’t be carried out without highly skilled and motivated personnel can withstand a tough competition. The purpose of the article is to assess the quality of "butler service" of accommodation facilities in Ukraine, comparison with foreign experience. Method. Methodical basis of the study are publications of domestic authors in the sphere of hotel industry, scientific periodicals, resources of Internet-network. Results. As a result of the research, the services of personal butlers in the most expensive hotels of the world have been analyzed. The general and extraordinary services of majordoms are presented. Scientific novelty. The basic requirements for personal butler in hotels are determined. The main problems of creating first-class personal butler services in Ukrainian hotels are analyzed. Practical significance. Additional luxury services are a key factor in competitiveness among 5 * hotels. In order to successfully provide additional services on the basis of the hotel, it is necessary to take into account, besides consumers, offers of competitive facilities, own resources, on the basis of which the company operates. To achieve a high level of competitive ability it’s necessary to provide a proper management, creative approach to work and the organization of unsurpassed additional services that meet the needs of the most demanding consumers.
Keywords: батлер; мажордом; особистий дворецький; персональний асистент; готельне підприємство; Butler; majordom; personal butler; personal assistant; hotel; кафедра готельно-ресторанної справи